Digital transformation effects and challenges for turning the disruptive opportunities to competitive advantage - Katsoulis, Dimitrios; Κατσούλης, Δημήτριος (2020)
During the last 20 years, the widespread adoption of digital technologies has forced businesses to adapt these technologies in order to differentiate their propositions, enhance their productivity and improve information analytics. Digital disruption is one of the key challenges that companies face and summarize the challenge as “disrupt or be disrupted”. To survive digital disruption, companies need to transform themselves into digital enterprises, therefore digital transformation is considered the ideal response to the threats of disruption and could be the decisive factor for achieving a sustainable business growth. The goal of this study is to contribute to the overall understanding of digital transformation and its challenges, providing further insights on how organizations can be benefited by adopting digital technologies in conjunction with differentiations in their business model, operational processes and culture. The conclusions of this study verify that digital transformation is a complicated endeavor which provides great potential for enhancing business results but has challenges and obstacles that every organization should overcome.